Rethinking Salafism: the transnational networks of Salafi ʻulama in Egypt, Kuwait and Saudi Arabia - Ismail, Raihan (Oxford University Press, 2021)
1. Introduction -- 2. Deconstructing Salafism -- 3. Transnational solidarity of Salafi ʻulama: the politics of Islamism -- 4. Transnational networks of Salafi ʻulama: the debate over the Sunni-Shiʻa divide -- 5. Transnational networks of Salafi ʻulama: haraki/quietist unity in the face of Jihadi Salafism? -- 6. Transnational networks of ʻulama: contesting the social sphere -- 7. Conclusion -- Notes -- Selected Bibliography.